Pengaruh Kompetensi Kepribadian Guru Pendidikan Agama Kristen terhadap Disiplin Belajar Siswa Kelas XI SMA Negeri 1 Sidamanik Tahun Pembelajaran 2023/2024 - Sri Rezeki Jelita Rajagukguk; Frainskoy Rio Naibaho; Goklas J. Manalu; Nisma Simorangkir; Boho Parulian Pardede (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to determine the positive and significant influence of the personality competence of Christian Religious Education teachers on the learning discipline of class XI students of SMA Negeri 1 Sidamanik in the 2023/2024 academic year. Quantitative research method with inferential statistics, because the research conducted is a sample study and the results are applied to the population. The population is all class XI students of SMA Negeri 1 Sidamanik who are Protestant Christians, consisting of 185 students and a sample of 46 people was determined using random sampling. The research instrument is a closed questionnaire. The results of the data analysis study obtained: a) Test of influence rcount = 0.399 > rtable = 0.291; b) Significance test tcount = 2.904 > ttable = 2.021; c) Regression equation Ŷ = -1.0477327 + 1.15131265X; d) The coefficient of determination test shows that the effect is 15.9%; e) Hypothesis test obtained Fcount = 8.35 > Ftable = 3.23 then H0 is rejected and Ha is accepted. The study concluded that there is a positive and significant influence between the personality competence of Christian Religious Education teachers on the learning discipline of class XI students of SMA Negeri 1 Sidamanik in the 2023/2024 Academic Year.